The Neonatal Autopsy: Can It Be Revived? - Swinton, Cameron H.; Weiner, Julie; Okah, Felix A. (American Journal of Perinatology, 2013)
Objectives To describe the trend and factors associated with the autopsy over the past decade at a level III neonatal intensive care unit (NICU) where all patients are presented with an option.Study Design Retrospective study of the autopsy in a cohort of infants who died in the NICU from January 1, 2001, to December 31, 2010.Results Of 446 deaths, 33.9% received the autopsy and rates decreased from the 2 years prior to the study. The autopsy was associated with gestational age at birth and chronologic age at death. On multivariable logistic regression analyses, the odds of an autopsy increased with gestational age (p = 0.001), death in the postneonatal period (odds ratio [OR] = 2.01, 95% confidence interval [CI] = 1.28, 3.16), and absence of a major congenital anomaly (OR = 1.96, 95% CI = 1.22, 3.23).Conclusion Autopsy rates continue to decline despite ensuring that all parents are presented with the option. Infants born at term and those who die after 1 month without known congenital anomalies are most likely to receive the autopsy. The persistently low rates may highlight the importance of helping families understand that the autopsy has utility even when the cause of death may appear to be obvious.
Keywords: autopsy rate; autopsy consent; neonatal death